Neoproterozoic 40Ar/39Ar mica ages mark the termination of a billion years of intraplate reworking in the Capricorn Orogen, Western Australia - Piechocka, A.; Sheppard, Steve; Fitzsimons, Ian; Johnson, S.; Rasmussen, Birger; Jourdan, Fred (Elsevier BV, 2018)
The tectonic history of the Proterozoic Capricorn Orogen, Western Australia, records complex intraplate reworking lasting nearly one billion years. Although the Paleo-Mesoproterozoic reworking history is well defined in the crystalline basement of the Gascoyne Province, at the western end of the orogen, the younger reactivation history remains unclear. Four reworking events affected the orogen at 1820–1770 Ma, 1680–1620 Ma, 1320–1170 Ma, and 1030–900 Ma. These events were succeeded by a breakout in predominantly dextral strike-slip reactivation of major shear zones across the Gascoyne Province. Currently, the age of this reactivation is constrained by only one date of c. 570 Ma from a single shear zone, but field relationships imply that some of the shear zones must be older than a suite of c. 755 Ma dolerite dykes. In order to constrain the age of fault and shear zone reactivation we obtained new 40 Ar/ 39 Ar dates for mica and in situ SHRIMP U-Pb dates for xenotime within shear zones. Our results when combined with previously published data, show that reactivation occurred between 920 and 830 Ma. These dates overlap with the youngest reworking event, the 1030–900 Ma Edmundian Orogeny. Furthermore, Neoproterozoic U-Pb phosphate ages are known from the bounding cratons and faulting within the adjacent Mesoproterozoic sedimentary basins suggest this event is of regional significance. In contrast to previous suggestions that this Neoproterozoic reactivation was the result of a collision from the west, we propose that it reflects north–south compression that caused dextral strike-slip fault reactivation in the north and exhumation of the southern part of the orogen.